2017
DOI: 10.5558/tfc2017-012
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial systems for precision forest inventory purposes: A review and case study

Abstract: Unmanned Aerial Systems (UAS) are capable of improving the efficiency of acquisition and providing fine spatial scale data for sustainable resource management. In this paper we begin by describing differences between UAS airframes, their successes and limitations, and list contemporary research applications. UAS compatible sensor technologies are discussed, including passive and active sensors. Finally, we detail a case study where UAS updated an Enhanced Forest Inventory (EFI) for a study area in interior Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
94
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 37 publications
1
94
0
2
Order By: Relevance
“…Recent studies have reported the use of UAS in various analyses, including forestry applications [27,28]. Collecting aerial photos by UAS and processing them with the structure from motion (SfM) method is one of the major new approaches to analyzing forest structures [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the use of UAS in various analyses, including forestry applications [27,28]. Collecting aerial photos by UAS and processing them with the structure from motion (SfM) method is one of the major new approaches to analyzing forest structures [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, the use of unmanned aerial vehicles (UAVs) in support of forest science has increased rapidly [37][38][39]. The use of UAVs has enabled the on-demand collection of high spatial resolution imagery, serving to improve the resolution of photogrammetric point clouds, and therefore offer improved characterization of forest structure [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…In [37], it was suggested that UAVs could be used in identifying forest areas in need for management, such as thinning or fertilizer to concentrate activities for those and increase efficiency that way. Similarly in assessing biodiversity, UAVs can be seen as support tool when planning field campaigns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small unmanned aerial vehicles (UAVs) have been used increasingly as a data collection option to support forest sciences and applications (Goodbody et al 2017, Pajares 2015, Torresan et al, 2017. The use of UAVs has enabled the on-demand collection of high spatial resolution imagery, serving to improve the resolution of photogrammetric point clouds, and therefore offer improved characterization of forest structure.…”
Section: Introductionmentioning
confidence: 99%